DESCRIPTION OF FACTORS THAT INFLUENCE NON-COMPLIANCE OF PPE USAGE AT GAS STATION ‘X‘ IN SURABAYA - Icha Pamelia (Journal of Industrial Hygiene and Occupational Health, 2019)
Non-compliance at work is a form of unsafe actions conducted by workers. Unsafe actions are able to endanger workers and other people around them. The act of workers that would not utilizing personal protective equipment (PPE) is an example of hazardous actions in the workplace. A good personal protective equipment is an equipment that is comfortable when used, provides effective protection against danger, and does not interfere with the work. Gas stations are one of the places that have high risk of exposure to chemicals, yet many workers are not compliant to use PPE. The purpose of this study is to find out the factors that make workers refuse to comply with the rule of PPE usage at work. This research is designed as a qualitative descriptive study. The method used for data collection consisted of interview, observation of employees’ behavior in the workplace, and documentation. The results showed that the non-compliance acts of the operating personnel at the gas station X in Surabaya were still high. The non-compliance in using PPE at the gas station X is influenced by the inconvenience of workers who feel hampered while serving consumers, knowledge, and the availability of PPE at work. Keywords: non-compliance, PPE, gas station